Suggestive Diagnostic Process in a Case of Multiple Myeloma with Gastrointestinal Immunoglobulin Light-Chain Amyloidosis Accompanied by Protein-Losing Enteropathy - Katsuya Endo; Takehito Ito; Jun Nomura; Keigo Murakami; Shiho Kondo; Tomonori Satoh; Daisuke Fukushi; Yuki Yoshino; Yoshiteru Sasaki; Atsuko Takasu; Takayuki Kogure; Morihisa Hirota; et al. (Case Reports in Gastrointestinal Medicine)
Multiple myeloma is a type of plasma cell neoplasm that produces monoclonal immunoglobulin. Multiple myeloma is known to cause immunoglobulin light-chain (AL) amyloidosis, which frequently involves the kidney and heart. Bone pain or fractures caused by osteolytic lesions and physical disorders related to renal or cardiac AL amyloidosis are major initial symptoms in multiple myeloma. Multiple myeloma diagnosed from the gastrointestinal symptoms is rare. We report a case of an 80-year-old man with multiple myeloma accompanied by gastrointestinal AL amyloidosis and secondary protein-losing enteropathy. The diagnostic process was suggestive, in that diarrhea and refractory leg edema related to protein-losing enteropathy were the primary symptoms and the trigger for making a sequential diagnosis of gastrointestinal AL amyloidosis and underlying multiple myeloma. This case is highly suggestive, in that multiple myeloma with gastrointestinal AL amyloidosis should be considered one of the background diseases of protein-losing enteropathy.